(untitled) (Perner’s Contacts, 2011)
Continuing problems of transport companies in consequence of financial and economic crisis are clear-cut evidence that risk management in transport companies plays a very important role to achieve long term competitiveness and profitability. The paper is dealing with business risks and risk management in transport companies.